Overall survival with cisplatin-gemcitabine and bevacizumab or placebo as first-line therapy for nonsquamous non-small-cell lung cancer: results from a randomised phase III trial (AVAiL) - Reck, Martin; von Pawel, J.; Zatloukal, P.; Ramlau, R.; Gorbounova, V.; Hirsh, V.; Leighl, N.; Mezger, J.; Archer, V.; Moore, N.; Manegold, Christian (Annals of oncology, 2010)
Background - Bevacizumab, the anti-vascular endothelial growth factor agent, provides clinical benefit when combined with platinum-based chemotherapy in first-line advanced non-small-cell lung cancer. We report the final overall survival (OS) analysis from the phase III AVAiL trial. - Patients and methods - Patients (n=1043) received cisplatin 80 mg/m2 and gemcitabine 1250 mg/m2 for up to six cycles plus bevacizumab 7.5 mg/kg (n=345), bevacizumab 15 mg/kg (n=351) or placebo (n=347) every 3 weeks until progression. Primary end point was progression-free survival (PFS); OS was a secondary end point. - Results - Significant PFS prolongation with bevacizumab compared with placebo was maintained with longer follow-up {hazard ratio (HR) [95% confidence interval (CI)] 0.75 (0.64-0.87), P=0.0003 and 0.85 (0.73-1.00), P=0.0456} for the 7.5 and 15 mg/kg groups, respectively. Median OS was >13 months in all treatment groups; nevertheless, OS was not significantly increased with bevacizumab [HR (95% CI) 0.93 (0.78-1.11), P=0.420 and 1.03 (0.86-1.23), P=0.761] for the 7.5 and 15 mg/kg groups, respectively, versus placebo. Most patients (∼62%) received multiple lines of poststudy treatment. Updated safety results are consistent with those previously reported. - Conclusions - Final analysis of AVAiL confirms the efficacy of bevacizumab when combined with cisplatin-gemcitabine. The PFS benefit did not translate into a significant OS benefit, possibly due to high use of efficacious second-line therapies.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.05.2023